Myxoma Atrium Kiri pada Kehamilan: Tantangan dalam Diagnosis dan Tatalaksana - Rony Mario Candrasatria,; Bambang Budi Siswanto; Nani Hersunarti; Rarsari Soerarso; BRM Ario S. Kuncoro; Amiliana M. Soesanto (The Indonesian Heart Association, 2014)
Primary tumors of the heart are rare where myxomas predominate as the most common type of primary cardiac tumors in all age groups. Even rarer, the incidence of myxomas during pregnancy is reported extremely low in the medical literature. The hemodynamic changes during pregnancy play an important role in influencing the clinical manifestation. The management is vary, depending on the week of gestation and risk assessment for both the mother and baby.We report a case of left atrial myxoma in 33-34 weeks of pregnancy. After judicious consideration, the patient was planned to have caesarian section at the full term pregnancy that will be followed one week after by tumor resection.